Handbook of Metalloproteins 2004
DOI: 10.1002/0470028637.met197
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear CopperA

Abstract: The purple CuA is a Cys‐bridged, mixed‐valence electron transfer center [Cu(1.5+)…Cu(1.5+)], found in cytochrome c oxidase and in nitrous oxide reductase. More recently, the NO reductase from Bacillus azotoformans was identified as the third CuA‐containing enzyme. There also exist engineered CuA sites which have been introduced by loop‐directed mutagenesis into blue type 1 copper proteins, such as azurin or amicyanin. Electron transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Two N(His) and two additional ligands (one S(Met) and one O carbonyl of a glutamate in C c O 1-3 or of a tryptophan in N 2 OR 4 ) in axial positions complete the coordination sphere. The purple color of the Cu A center is the result of predominant S(Cys) → Cu charge-transfer transitions at ∼480 and ∼530 nm and a broad class III mixed-valent charge-transfer band around ∼830 nm. , The delocalized mixed-valent configuration Cu 1.5 Cu 1.5 is consistent with the multifrequency EPR data . The well-resolved seven-line pattern evidences the unpaired electron interaction with two I = 3/2 copper centers as described for N 2 OR …”
Section: Introductionsupporting
confidence: 77%
“…Two N(His) and two additional ligands (one S(Met) and one O carbonyl of a glutamate in C c O 1-3 or of a tryptophan in N 2 OR 4 ) in axial positions complete the coordination sphere. The purple color of the Cu A center is the result of predominant S(Cys) → Cu charge-transfer transitions at ∼480 and ∼530 nm and a broad class III mixed-valent charge-transfer band around ∼830 nm. , The delocalized mixed-valent configuration Cu 1.5 Cu 1.5 is consistent with the multifrequency EPR data . The well-resolved seven-line pattern evidences the unpaired electron interaction with two I = 3/2 copper centers as described for N 2 OR …”
Section: Introductionsupporting
confidence: 77%
“…The Cu A center is found in numerous organisms as the electron entry point and transfer hub for aerobic (cytochrome c oxidase, C c O, and a terminal oxidase, SoxH, in Sulfolobus acidocaldarius ) and anaerobic (N 2 OR and nitric oxide reductase, NOR , ) respiration. Its unique coordination and electron transfer (ET) properties have generated great interest in the Cu A site. , While the Cu A center itself is natively found in small cupredoxin-like domains, these domains are associated in some cases with large, membrane-bound complexes and always with enzymes containing many other metallochromophores in the as-isolated form, which complicates studies of the Cu A site. , Thus, several systems have been developed to yield a soluble protein with a Cu A site that is free from other chromophores, including soluble truncates of native Cu A proteins and biosynthetic models. One such biosynthetic model, Cu A azurin (Cu A Az), was engineered from the blue copper cupredoxin, azurin, through loop-directed mutagenesis . Extensive spectroscopic, X-ray crystallographic, and electron transfer studies have shown Cu A Az to be an excellent electronic, structural, and functional model of native Cu A centers. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Cu A is a binuclear Cu center, similar to the one present in cytochrome c oxidases, 366,367 that is found within a loop of the cupredoxin fold at the C-terminus of NosZ. Two fully conserved Cys residues are the bridging ligands of the two Cu ions that lie 2.5 Å apart (Figure 35a).…”
Section: N 2 -Forming Enzymesmentioning
confidence: 93%
“…389 In its oxidized form, it is found in a mixed-valent [Cu A1 1.5+ : Cu A2 1.5+ ] state with a net charge of +3 and an S = 1 2 spin state, 375 similar to some HCOs. 366,390 In UV-vis absorption spectra of holoproteins, oxidized Cu A contributes absorption maxima at 480, 525-540, and 800 nm (Figure 39). The single unpaired electron that is fully delocalized over both Cu nuclei gives rise to a narrow seven-line hyperfine splitting in the g || region of EPR spectra, characteristic of two nuclear spins…”
Section: Cu a And Cu Z Electronicmentioning
confidence: 99%